Meditation - Satchidananda, Swami, 1914-2002. (Buckingham, Va. : Integral Yoga Publications, 2011)
Everything you need to know to become established in a lifelong practice of meditation, "the key to everything." A great yoga master instructs you in a thorough variety of approaches including meditation on a variety of mantras, on a form or symbol, and on self-enquiry. Instruction in powerful techniques such as combining sound vibrations with the inner flow of subtle energies and chakras, and ajapa japa--listening to the breath repeat the mantra. Plus instruction in the all-important techniques for preparation for meditation including pranayama, the yogic breathing practices. Plus an illuminating question and answer section. Short but thorough instruction in the central practice of all of yoga.
Keywords: Meditation; Yoga; BODY, MIND & SPIRIT / Meditation; RELIGION / Meditations; Electronic books